From magnifying glass to operative microscopy – the historical and modern role of the microscope in microsurgery - Liczbik, Oskar; Goertz, Sebastian; Wiśniewski, Jakub; Kurlandt, Patryk; Libionka, Witold; Adamski, Stanisław; Kloc, Wojciech (Polish Journal of Pathology, 2019)
The modern computer-assisted microscope, being a hallmark of microsurgery, has become a standard piece of equipment in the operating theatre. Its introduction enabled visualisation of fine anatomical structures, obscure to the unaided eye, and revolutionised many surgical specialties, such as neurological, ophthalmological, or vascular. These astounding achievements have been the culmination of a century of constant progress in optical engineering and microsurgery, since 1921, when a microscope was first used during surgery. Long before surgery, pathology adopted microscopes, and they have become its most prominent diagnostic tools. We traced the evolution of this important invention and discussed its present status and future prospects.